2017
DOI: 10.13005/ojc/330402
|View full text |Cite
|
Sign up to set email alerts
|

S-NICS Investigation for Heterocyclic Anticancer Compounds

Abstract: There are no works in theoretical of a statistical method of NICS-nucleus independent chemical shift for study of heterocyclic rings , since the asymmetry 15 (h) and skew 15 (k) parameter is fluctuated in small distance and are alternate in large distance in the center of heterocyclic rings . Through changing the asymmetries among 0< h< +1 skew 15 could be changed in the range of -1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…23 In attention to the applications of elastomeric nanocomposites, the considerable properties of the compound are viscoelastic and cure behavior mainly. 24 Many researches have been concluded that the optimum cure time of the rubbers filled with carbon reinforcements is lower than the unfilled ones. Reduction in the optimum cure time (t 10 ), thanks to the carbon-based fillers are played an accelerated role in the reaction between the sulfur and rubber compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In attention to the applications of elastomeric nanocomposites, the considerable properties of the compound are viscoelastic and cure behavior mainly. 24 Many researches have been concluded that the optimum cure time of the rubbers filled with carbon reinforcements is lower than the unfilled ones. Reduction in the optimum cure time (t 10 ), thanks to the carbon-based fillers are played an accelerated role in the reaction between the sulfur and rubber compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Stress relaxation is the decay of stress with time under conditions of constant strain. Mohammadian-Gezaz and Karrabi 24 reported that in natural rubber (NR) compounds filled with organoclay (OC), with raising nanoparticle content, led to a higher initial relaxation modulus. In another study, they concluded that the enhancing of OC to the NR compounds increased both the elastic and viscous slopes in the relaxation curve, which is the cured samples had a higher elastic slope and a lower viscous slope than uncured ones.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compound played a vital actions in the metabolism of all cells; 6 (or sometimes 5) membered hetero-cycles including one to three heteroatoms. Recently, imidazole fragment has been attracting much concentration because of its role as attractive scaffold for biochemical active heterocyclic drugs (Mohammadian, N. K. et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Electrical conductivity of the Na-GO increases, Because of the electron donor nature of the Na 33 . Based on some previous studies we have used several methods to simulate the NIBs and calculated the NMR, solvent effect 24 , voltages, charges and physical properties of our model [32][33][34][35][36][37][38][39][40][41][42][43][77][78][79][80][81] .Typical commercially 31 used sodium -ion battery including several interconnected 32 electrochemical cells, where each one consist of a GO anode, a cathode formed 30 by sodium metal oxide (NaCoO 2 ) and electrolyte same as NaPF 6 embedded in a separator felt 29 . In liquid phase, the temperature related of diffusion 45 is less than the solid form.…”
Section: Introductionmentioning
confidence: 99%